IDENTIFICATION OF SHEAR WAVE VELOCITY (VS) USING MICROTREMOR DATA FOR SUBSURFACE SITE CHARACTERIZATION IN PALU CITY - Pramesti, Widya
The Palu-Donggala earthquake that occurred on September 28, 2018, was a result of the Palu Koro fault activity. The earthquake was magnitude Mw 7.5 with the epicenter in Donggala Regency and had a very damaging impact on the City of Palu. The population density in Palu City resulted in high casualties due to the incident. The damage caused by an earthquake is related to the characteristics of the subsurface somewhere. To characterize the subsurface of the city of Palu, microtremor data was measured at 22 points covering the entire city of Palu for three months from February to May 2015. To map the subsurface dynamic characteristics in the form of dominant frequency and amplification, the Horizontal-to-Vertical Spectral Ratio (HVSR) method was used. Inversion using the Monte Carlo method is carried out to determine the value of shear wave velocity (Vs) and depth of engineering bedrock in Palu City, and then calculate the shear wave velocity on average 30 meters below the surface (Vs30) to classify soil types in Palu City. From the dominant frequency map produced, it was concluded that in the north to the southeast of Palu City is an area that has a low dominant frequency which indicates that there is a thick layer of sediment. The amplification map shows that in the northern area of the City of Palu it gives a high amplification value. This is related to the results of the dominant frequency map because thick sediments will provide high earthquake wave amplification values. The inversion results show that there is a basin structure filled with sediment in the north to the southeast of Palu City and has a greater thickness than the western part of Palu City. The type of soil in the first 30 meters of Palu City in the north to the southeast, in general, is in the form of soft soil (SE) while in the City of Palu the south to the southwest is generally in the form of medium (SD). Furthermore, by comparing the affected areas of the Palu-Palu earthquake in 2018, it shows that the research data obtained is following the area of damage.